A Review of Morphomeristic Characterization and Classification of Genus Enteromius spp in Africa - Jepleting, H.; Wanga, J.; Chemoiwa, E. J.; Barasa, J. (Africa Environmental Review Journal, 2022)
Enteromius is currently represented by 350 valid species, making it the most speciose and widely distributed cyprinid genus on the African continent. The Enteromius represents one of the most common genera occurring in almost all river systems across the continent, these fishes are generally difficult to identify because of their very similar body morphology and color pattern, coupled with the lack of revision within the group. Despite this, there are many challenges to adequately conserve the Enteromius because of unsatisfactory taxonomic knowledge of important portions of the genus. In this review, distinctive morphometric characteristics, general characterization and classification of the genus Enteromius occurring in Africa was analyzed. It was established that many species under the genera Enteromius have been mis-identified giving a false impression among the taxa richness. Genus Enteromius is distinguished from other small African diploid smiliogastrin genera distributed in African water bodies (Barboides, Clypeobarbus Barbopsis) based on differences in morphomeristic characteristics. Most occurring differences among Enteromius species are dorsal-fin placement in comparison to anal-fin origin, number of dorsal-fin rays, number of paired nostrils on either side of the snout, eye size, placement in the orbital rim and pigmentation pattern, shape and pattern of mid-lateral scale row. Isolated studies with focusing on a single geographical location resulting to double identification. Since fish under the genera Enteromius spp are sensitive to habitat quality and occurs mostly in small water bodies and headwater streams, the need to conserve catchments to enhance biodiversity.